2013
DOI: 10.1097/spv.0b013e3182a331a9
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Homing Factor, CCL7, Expression in Mouse Models of Stress Urinary Incontinence

Abstract: Objectives Animal models of vaginal distention (VD) have demonstrated increased expression of chemokine (C-C motif) ligand 7 (CCL7). In this study, we investigated the expression of CCL7 in mice models of simulated birth trauma-induced urinary incontinence utilizing VD and pudendal nerve transection (PNT). Methods Forty-nine mice were divided into 6 groups: VD, sham VD, PNT, sham PNT anesthesia, and age-matched controls. The urethra, vagina, and rectum were harvested for the expression of CCL7 immediately or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…13 the cytokines involved include stromal cell-derived factor-1 (sDf-1, also known as CXCL12) 14 and monocyte chemo-attractant protein 3 (MCP-3, also known as CCL7). 15,16 CXCL12 and its receptor CXCR4 are crucial in regulating mesenchymal stem cell survival and differentiation. 17 in our preliminary studies, we have evaluated these cytokines in the anal sphincter and found that direct anal sphincter injury results in upregulation of CXCL12 and CCL7 expression soon after injury 18 and also after electrical stimulation.…”
mentioning
confidence: 99%
“…13 the cytokines involved include stromal cell-derived factor-1 (sDf-1, also known as CXCL12) 14 and monocyte chemo-attractant protein 3 (MCP-3, also known as CCL7). 15,16 CXCL12 and its receptor CXCR4 are crucial in regulating mesenchymal stem cell survival and differentiation. 17 in our preliminary studies, we have evaluated these cytokines in the anal sphincter and found that direct anal sphincter injury results in upregulation of CXCL12 and CCL7 expression soon after injury 18 and also after electrical stimulation.…”
mentioning
confidence: 99%
“…These time points were selected based on the timecourse of cytokine expression in previous studies. 7,9,22,25,26 Loxl1 KO mouse gestation duration is approximately 21 days, so, as a feasible time point for studying the effects of pregnancy in the absence of delivery as a control for delivered mice, tissues were harvested on the 20 th day of gestation, prior to parturition for the pregnant group (Figure 1A). Sixty-four additional age-matched virgin Loxl1 KO female mice were utilized as sham cesarean injury controls or unmanipulated virgin controls (Figure 1A).…”
Section: Methodsmentioning
confidence: 99%
“…46 However, little research has been conducted to elucidate molecular markers for maternal injury in genitourinary tissues during the peripartum period that might provide insight into the mechanisms of injury that could lead to POP. 79 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell therapy and tissue engineering are among the newest strategies under investigation for the treatment and prevention of SUI [46]. The therapeutic use of stem cell therapy in SUI is based on two broad approaches: (1) skeletal muscle regeneration using adult muscle-derived progenitor-cell therapy after injury, and (2) repair/prevention using stem cell therapy at the time of injury or initiation of the phenotype [79]. While the first approach relies on the ability of the stem cell to engraft and differentiate, the reparative approach depends on the paracrine and anti-inflammatory function of the stem cell.…”
Section: Introductionmentioning
confidence: 99%